2020
DOI: 10.2147/ccid.s257647
|View full text |Cite
|
Sign up to set email alerts
|

<p>IL-33/13 Axis and IL-4/31 Axis Play Distinct Roles in Inflammatory Process and Itch in Psoriasis and Atopic Dermatitis</p>

Abstract: Background: Pruritus is the most common symptom in patients with skin disease. Psoriasis and atopic dermatitis are clinically distinct inflammatory diseases. Interleukins are cytokines which play key roles in inflammatory signaling pathways. Materials and Methods: Cross-sectional study was conducted among patients with psoriasis and atopic dermatitis: 59 psoriatic patients, 56 AD patients, and 49 matched healthy controls. Interleukins 4, 13, 31, 33 serum levels were assayed by ELISA and results were compared u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 32 publications
(35 reference statements)
1
25
0
2
Order By: Relevance
“…IL-31/IL-31RA interaction activates signal transduction pathways leading to expression and release of various chemokines, proinflammatory cytokines, regulation of cell proliferation and stimulation of DRG neurons that play important role in pruritus induction and inflammatory diseases ( 72 74 ). A number of researchers observed an association between IL-31 and inflammatory skin diseases with severe pruritus including AD ( 61 , 75 ), bullous pemphigoid ( 76 ), cutaneous T-cell lymphoma ( 77 ), CSU ( 78 ) and psoriasis ( 79 ). Regarding treatment approaches, a successful therapy of urticaria using omalizumab led to decreased serum levels of IL-31 ( 80 ).…”
Section: Receptors In Neuro-immune Interactionsmentioning
confidence: 99%
“…IL-31/IL-31RA interaction activates signal transduction pathways leading to expression and release of various chemokines, proinflammatory cytokines, regulation of cell proliferation and stimulation of DRG neurons that play important role in pruritus induction and inflammatory diseases ( 72 74 ). A number of researchers observed an association between IL-31 and inflammatory skin diseases with severe pruritus including AD ( 61 , 75 ), bullous pemphigoid ( 76 ), cutaneous T-cell lymphoma ( 77 ), CSU ( 78 ) and psoriasis ( 79 ). Regarding treatment approaches, a successful therapy of urticaria using omalizumab led to decreased serum levels of IL-31 ( 80 ).…”
Section: Receptors In Neuro-immune Interactionsmentioning
confidence: 99%
“…Among the tested cytokines (IFN-ɣ, TNF-α, IL-1α, IL-1β, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12) only IL-2, a SP-induced cytokine that triggers the maturation of T cells, was significantly increased in pruritic psoriatic skin [ 7 ]. Other cytokines, such as IL-4, IL-13, IL-31 and IL-33 play a key role in the pro-inflammatory and anti-inflammatory signaling pathways in patients suffering from inflammatory skin diseases such as psoriasis or atopic dermatitis [ 19 ]. In 2020, Badoor et al published results of a study evaluating the correlation between serum concentration of IL-4, IL-13, IL-31 and IL-33 and intensity of pruritus in psoriasis and atopic dermatitis.…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, Badoor et al published results of a study evaluating the correlation between serum concentration of IL-4, IL-13, IL-31 and IL-33 and intensity of pruritus in psoriasis and atopic dermatitis. In patients with psoriasis, similarly to atopic dermatitis, the levels of IL-4 and IL-31 were significantly elevated in comparison to healthy controls [ 19 ]. These findings were compatible with the results of another study in which elevated levels of IL-31 in the skin or serum of patients with psoriasis were demonstrated [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also growing knowledge regarding the immune-mediated pathomechanism of AD, and the osteoimmunology has highlighted the cross-regulation of bone and the immune system, which involving various cell types, signaling pathways, cytokines, and chemokines, under both homeostatic and pathogenic conditions (31)(32)(33). Since many cytokines and immune cell types have been found to be active in AD and play a role in bone remodeling, which may help to elaborate on how immuneassociated diseases affect osteoimmunology and lead to bone loss (32)(33)(34)(35)(36)(37)(38). Besides, a number of studies have found that Vitamin D deficiency is more prevalent in patients with AD and correlated with the severity of the disease, and extra supplementation of Vitamin D could result in a clinically meaningful AD severity reduction (39).…”
Section: Possible Mechanismsmentioning
confidence: 99%